2021
DOI: 10.1002/pds.5266
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide and risk of melanoma subtypes

Abstract: Background Hydrochlorothiazide (HCTZ), a common diuretic known to be photosensitizing and previously associated with non‐melanoma skin cancer, was recently reported to be associated with two melanoma subtypes, nodular and lentigo, among residents of Denmark. Our goal was to examine whether Danish findings could be replicated in a US cohort, using a similar study design and analysis. Methods Among non‐Hispanic White enrollees of Kaiser Permanente Northern California, we conducted an analysis of 9176 melanoma ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
3
11
0
2
Order By: Relevance
“…Our study indicated an increased risk for NMSC associated with the use of hydrochlorothiazide but not with bendroflumethiazide or indapamide. Specifically, we found a higher risk for SCC than for BCC associated with thiazide use, consistent with evidence that cumulative UV exposure plays a greater role in the aetiology of SCC than of BCC [ 35 , 36 ]. The minimum average daily UV exposure level to induce skin cancers among thiazide users is unclear; however, one Icelandic study indicated that relatively low levels of average daily UV exposure were sufficient to cause 1.24-fold and 1.14-fold increases in the risks of SCC in situ and BCC, respectively, following hydrochlorothiazide use [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Our study indicated an increased risk for NMSC associated with the use of hydrochlorothiazide but not with bendroflumethiazide or indapamide. Specifically, we found a higher risk for SCC than for BCC associated with thiazide use, consistent with evidence that cumulative UV exposure plays a greater role in the aetiology of SCC than of BCC [ 35 , 36 ]. The minimum average daily UV exposure level to induce skin cancers among thiazide users is unclear; however, one Icelandic study indicated that relatively low levels of average daily UV exposure were sufficient to cause 1.24-fold and 1.14-fold increases in the risks of SCC in situ and BCC, respectively, following hydrochlorothiazide use [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Briefly, because hydrochlorothiazide was less likely to be prescribed as the drug of choice for antihypertensive treatment, following up patients from the first date of hydrochlorothiazide may lead to a spurious protective effect against skin cancers because participants were free from the outcome of skin cancer (i.e., immortal time) until they received hydrochlorothiazide. Finally, 13 case-control studies [ 6 , 7 , 11 , 13 , 14 , 36 – 43 ] and 5 cohort studies [ 10 , 12 , 44 46 ] with a total of 17,848,313 participants, with 6,790,008 exposed to thiazides, were included, and most of the studies analysed hydrochlorothiazide-containing drugs. The summary for the inclusion of thiazides is presented in Additional file 1 : Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations